Exploring geographic differences in IgE response through network and manifold analyses. - Cucco,A; Pearce,N; Simpson,A; Pembrey,L; Mpairwe,H; Figueiredo,CA; Cooper,PJ; Douwes,J; Brooks,C; Adcock,IM; Kermani,NZ; Roberts,GDM; et al. (J Allergy Clin Immunol, 2026)
BACKGROUND: Component-resolved diagnostics allow detailed assessment of IgE sensitization to multiple allergenic molecules (component-specific IgEs, or c-sIgEs) and may be useful for asthma diagnosis. However, to effectively use component-resolved diagnostics across diverse settings, it is crucial to account for geographic differences. OBJECTIVE: We investigated spatial determinants of c-sIgE networks to facilitate development of diagnostic algorithms applicable globally. METHODS: We used multiplex component-resolved diagnostics array to measure c-sIgE to 112 proteins in an international collaboration of several studies: WASP (World Asthma Phenotypes; United Kingdom, New Zealand, Brazil, Ecuador, and Uganda), U-BIOPRED (Unbiased Biomarkers for the Prediction of Respiratory Disease Outcomes; 7 European countries), and MAAS (Manchester Asthma and Allergy Study, a UK population-based birth cohort). Hierarchical clustering on low-dimensional representation of co-occurrence networks ascertained sensitization and c-sigE clusters across populations. Cross-country comparisons focused on a common subset of 18 c-sIgEs. We investigated sensitization networks across regions in relation to asthma severity. RESULTS: Sensitization profiles shared similarities across regions. For 18 c-sIgEs shared across study populations, the response structure enabled differentiation between different geographic areas and study designs, revealing 3 clusters: (1) Uganda, Ecuador, and Brazil, (2) U-BIOPRED children and adults, and (3) New Zealand, United Kingdom, and MAAS. Spectral clustering identified differences between clusters. We observed constant, almost parallel shifts between severe and nonsevere asthma in each country. CONCLUSIONS: Patterns of c-sIgE response reflect geographic location and study design. However, despite geographic differences in c-sIgE networks, there is a remarkably consistent shift between networks of subjects with nonsevere and severe asthma.